Multidisciplinary methodology proposal for the biogeographic Evaluation of Natura 2000 Network Areas in the Basque Country. The example of Gárate-Santa Bárbara (Guipúzcoa) - José Antonio Cadiñanos Aguirre Pedro Jo (Boletín de la Asociación de Geógrafos Españoles)
Resumen